CELIE SUFFERING IN THE NOVEL THE COLOR PURPLE BY ALICE WALKER - Nurbayani, Yuni (Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
ABSTRACT The main problem of this research is the way in which the suffering experienced by the character Celie and the form of suffering with the study of literary psychology that is reflected in the novel The Purple Color by Alice Walker. The source of the research data is Alice Walker’s novel The Color Purple. The data sources used were primary and secondary data. Primary data sources are the Color Purple novel itself and secondary data sources are other sources related to the analysis, such as author biographies and other relevant information. This research method uses qualitative descriptive methods. In the analysis of the novel The Color Purple, the data analysis technique used in this research is an approach of literary psychology that focuses on the psychology of the main character Cellie with the following steps: data classification, data analysis, data description, and data interpretation. The results of this study indicate that the main character Celie experiences various kinds of suffering ranging from physical, psychological, even sexual suffering.This study aims to describe the suffering experienced by Celie’s characters and forms of suffering with a study of literary psychology as reflected in Alice Walker’s novel The Color Purple.Keywords: Main character, Novel, Suffering